Kabuki syndrome: international consensus diagnostic criteria. Issue 2 (4th December 2018) - Adam, Margaret P; Banka, Siddharth; Bjornsson, Hans T; Bodamer, Olaf; Chudley, Albert E; Harris, Jaqueline; Kawame, Hiroshi; Lanpher, Brendan C; Lindsley, Andrew W; Merla, Giuseppe; Miyake, Noriko; Okamoto, Nobuhiko; et al.
Abstract : Background: Kabuki syndrome (KS) is a clinically recognisable syndrome in which 70% of patients have a pathogenic variant in KMT2D or KDM6A . Understanding the function of these genes opens the door to targeted therapies. The purpose of this report is to propose diagnostic criteria for KS, particularly when molecular genetic testing is equivocal. Methods: An international group of experts created consensus diagnostic criteria for KS. Systematic PubMed searches returned 70 peer-reviewed publications in which at least one individual with molecularly confirmed KS was reported. The clinical features of individuals with known mutations were reviewed. Results: The authors propose that a definitive diagnosis can be made in an individual of any age with a history of infantile hypotonia, developmental delay and/or intellectual disability, and one or both of the following major criteria: (1) a pathogenic or likely pathogenic variant in KMT2D or KDM6A ; and (2) typical dysmorphic features (defined below) at some point of life. Typical dysmorphic features include long palpebral fissures with eversion of the lateral third of the lower eyelid and two or more of the following: (1) arched and broad eyebrows with the lateral third displaying notching or sparseness; (2) short columella with depressed nasal tip; (3) large, prominent or cupped ears; and (4) persistent fingertip pads. Further criteria for a probable and possible diagnosis, including a table of suggestive clinical features, are presented. Conclusion: As targeted therapies for KS are being developed, it is important to be able to make the correct diagnosis, either with or without molecular genetic confirmation.